Implementation of ABC and ROP Methods for Inventory Control of Mandatory Pharmacy Drugs - Nur Izani Maulani; Selly Anastassia Amellia Kharis (G-Tech: Jurnal Teknologi Terapan, 2025)
Grawira Farma Pharmacy in Kulon Progo manages Mandatory Pharmacy Drugs, which require strict regulation for self-medication. Managing the inventory of Mandatory Pharmacy Drugs is necessary to prevent shortages and stockouts. This study aims to analyze the planning and control of Mandatory Pharmacy Drugs inventory at Grawira Farma Pharmacy, using the Always Better Control (ABC) method for inventory planning, categorizing drugs into three groups. Group A consists of fast-moving drugs with 11 types (27.5%), accounting for 79.38% of total drug usage and an investment value of Rp 1,697,300.00, group B consists of moderately-selling drugs with 11 types (27.5%),  contributing 18.29% of total drug usage and an investment value of Rp 1,319,450.00, and group C consist of the slowest-selling drugs with 18 types (45%), representing 2.33% of total drug usage and an investment value of Rp 392,425.00. In addition to inventory planning, this study examines inventory control using the Reorder Point (ROP) method to determine when the reorder after grouping Mandatory Pharmacy Drugs. The research results obtained the reorder point of Mandatory Pharmacy Drugs, which include group A, ranging from 150-500 items, group B varies from 14-340 items, group C, ranging from 0-34 items.